Potential for utilizing indigenous knowledge to sustainably improve reproduction efficiency of cattle in sub-Saharan Africa: a narrative review - Raphalalani, Zwivhuya Constance; Malatji, Dikeledi Petunia; Chimonyo, Michael (Frontiers in Sustainable Food Systems, 2025)
Low-input cattle production systems are characterized by low reproductive efficiency that reduces herd productivity which in turn affects food security. Conventional ways of improving cattle reproduction have been effective but not sustainable in low-input cattle production systems. These interventions follow a top-down approach with procedures based on successes from high-input production systems which have appropriate infrastructure and trained personnel. There are indigenous approaches which farmers in low-input production systems use to manage their herds, set breeding goals, design mating systems and manage reproductive challenges. This narrative review explores the potential of utilizing this indigenous knowledge in integrated strategies to improve cattle reproductive efficiency in sub-Saharan Africa. An extensive review of existing global literature that explored indigenous knowledge on cattle reproductive management as well as closely related integration studies was conducted. It was found that resource-limited farmers select breeding cattle using traits that improve and maintain the herd’s survivability and adaptability such as a white coat color being preferred for easy traceability in deep forest and bull body size associated with masculinity. They use indigenous remedies to improve reproductive health such as oral administration of Elephant’s root and Velvet Bushwillow to prevent and cure dystocia, treating retained placenta and clearing infections which may cause abortion in cows. Furthermore, farmers select fast growing bulls which indicate their dam’s superior mothering ability and heifers with a pelvis that has a wide sloped rump for easier calving. Pregnancy evaluation is mostly visual with udder and abdominal growth which indicate prominent milk production and fetal growth. Challenges that hinder the adoption of these approaches should be addressed and policies that recognize these indigenous strategies should be developed and promoted.